(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Maximenko I. G., Pinskaya E. L. Elocution as a component of teachers’ speech skills. The article shows the essence of elocution and its content. The author characterizes structural components and highlights the role of elocution in teaching, typical mistakes and substantiates the ways of its forming.